Actual problems of eating disorders and ways to solve them - V. Patonich (Mukachevo State University, 2024)
As eating disorders become more and more common, it is necessary to understand the influence of modern life factors on the formation of these diseases in order to develop more effective strategies for their prevention and treatment, so the purpose of this study was to systematically examine the sociocultural and psychological factors of eating disorders. Two key methodological approaches were used to study the social and underlying psychological factors of these disorders: sociocultural and psychoanalytic. The empirical basis of the study is based on the interview method. Social factors, in particular media influence, determine the formation of eating disorders, especially among women, through the creation of negative standards of beauty and bodily satisfaction. Based on interviews with people with eating disorders, it was found that the underlying psychological factors of these disorders are mainly focused on intrapersonal aspects, such as the perception of food and one's own body, emotional sphere, and self-esteem. At the same time, interpersonal factors related to interaction with the environment have a lesser impact. These factors can lead to the development and complicate the course of eating disorders, so it is important to work with psychological aspects for effective treatment. It is substantiated that psychodynamic and Gestalt therapy are effective treatment methods aimed at resolving mental conflicts. Both approaches use a variety of methods, including dream analysis and fissiotherapy, to help patients understand and resolve their emotional and behavioural interactions with food. The practical value of the study is that its results highlight the need to use psychodynamic and Gestalt approaches in therapy, which can address the underlying psychological and emotional factors of eating disorders. The study can be applied in the activities of institutions specializing in the treatment of eating disorders